2003
DOI: 10.1046/j.1365-2230.2003.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe generalized argyria secondary to ingestion of colloidal silver protein

Abstract: Argyria is a rare cause of cutaneous discolouration caused by silver deposition. We report a case of dramatic and diffuse argyria secondary to ingestion of colloidal silver protein over a 1-year period. Stained electron microscopy with spectral analysis was used to confirm the clinical diagnosis. Silver-protein complexes are deposited in the skin and reduced to inert silver salts by sunlight in a process similar to that harnessed in photography. Our patient had obtained the silver for consumption via mail orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
120
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 9 publications
0
120
0
4
Order By: Relevance
“…The antifungal potential of AgNP shows coherence with broad spectrum activity, multiple cellular targets and minimum host toxicity. However, silver is reported to be toxic at a high concentration and its persistent use causes argyrosis and argia [9,10]. Therefore, the requirement is towards exploring novel biocompatible nanomaterials with effective anti-biofilm and optical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal potential of AgNP shows coherence with broad spectrum activity, multiple cellular targets and minimum host toxicity. However, silver is reported to be toxic at a high concentration and its persistent use causes argyrosis and argia [9,10]. Therefore, the requirement is towards exploring novel biocompatible nanomaterials with effective anti-biofilm and optical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, argyria as a result of taking silver-containing supplements has been reported many times. [5][6][7][8][9][10][11] Because of the striking appearance of the blue-grey discolouration of sun-exposed area, argyria is easily suspected clinically. However, causative agents should be confirmed by analysis of EDX through SEM examination.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably because some of the A-type tissues resembled B-type tissue in the mid stage or that some sulfuration had occurred in the short term. Selenium, having the same chemical property as S, has been found to exist with Ag in pigmentation cases 13,28) . However, Se was not found in our experiment.…”
Section: Sulfuration Of Silvermentioning
confidence: 99%
“…In the case of argyria, White et al 13) demonstrated the presence of silver with S and Se in the base membrane and elastic fibers. Aoyagi and Katagiri 17) also reported the existence of silver and S in connective tissue without host reaction.…”
Section: Sulfuration Of Silvermentioning
confidence: 99%
See 1 more Smart Citation